Impact of Agglomeration Economies on Productivity of Pharmaceutical Firms of Himachal Pradesh - Himanshu; Anand, Dilasha (Arthshastra Indian Journal of Economics & Research, 2019)
This paper used Levinsohn and Petrin's methodology to assess the productivity performance of the pharmaceutical manufacturing firms of the state of Himachal Pradesh over the period from 2001-2002 to 2015-2016. Further, a fixed effects approach has been brought into use to determine the impact of various agglomeration variables on the total factor productivity of Himachal Pradesh's pharmaceutical manufacturing firms. The total factor productivity of Himachal Pradesh’s pharmaceutical firms showed an unsteady performance over the period under study. It was observed that while urbanization has helped increase the productivity of pharmaceutical firms of the State, after a certain level, diseconomies arising from increasing urbanization tend to affect the productivity of firms adversely. Although intraindustry localization tended to impact productivity of the firms negatively, the concentration of a variety of industries affected the productivity of the firms positively.